The Effect of Plyometric Training on the Development of Explosive Power, Speed–Strength of the Legs, and Long-Range Shooting Skill in Female Futsal Players - Saddam Mohammed Ahmed (Indonesian Journal Publisher, 2026)
The importance of this study lies in its ability to improve the physical performance of athletes based on their ability to develop muscles' strength through training. In general, the ability to perform any required skill efficiently, accurately, and for prolonged periods without getting tired depends mainly on muscular strength. This may be attained through adopting appropriate techniques of training associated with muscular strength development such as plyometric training. The problem addressed through this study is the low level of explosive power and speed-strength of female futsal players leading to poor performances in physical and technical aspects of game play and hence unfavorable results in terms of winning or losing matches. Additionally, the limitation affects the speed and force with which the player performs some required skills during the game. The purpose of this study was to examine the influence of plyometric training on developing explosive power, leg speed-strength, and long-range shooting skills of female futsal players. The design used in this study was an experimental one owing to the appropriateness of this design to address the research problem. The study involved 12 female participants from the Diyala Directorate of Education futsal team at secondary schools. From the findings obtained, it has been established that there were significant effects resulting from plyometric training in terms of developing certain types of muscular strength and long-range shooting skills among futsal players